UPAYA PEMECAHAN MASALAH PIS-PK MELALUI PARTISIPASI MASYARAKAT DENGAN PENGEMBANGAN POTENSI DAN SUMBER DAYA LOKAL DALAM MENCAPAI KELURAHAN SEHAT - Muniarti Muchtar; Yessi fadriyanti; Yosi Suryarinilsih; Lola Felnanda; Delima Delima; Asep Irfan (P3M Universitas Aisyiyah Surakarta, 2023)
The Healthy Indonesia Program is one of the government's flagship programs to create healthy families, in determining a healthy family it can be seen from the 12 indicators of a healthy family. Problems that arise in healthy families can be solved with the PIS-PK approach. The purpose of this community service is to be able to solve PIS_PK problems through community participation by developing local potential and resources in achieving healthy urban villages in the new normal period. The methods used in this community service include providing education and assistance, making IT-based educational media and developing potential and local resources related to PIS-PK and the management of Covid-19. The result of this community service is that most of the knowledge of the people of kurao pagang, surao gadang and desert laweh is high after the intervention. The development of local potential and resources has been carried out by making masks at the embroidery tailor convection and distributing masks in Surau Gadang, desert laweh and kurao pagang.